2014
DOI: 10.14503/thij-13-3695
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous Repair of Post-Myocardial Infarction Ventricular Septal Defect: Current Approaches and Future Perspectives

Abstract: Post-myocardial infarction ventricular septal defect is a devastating complication of STelevation myocardial infarction. Although surgical intervention isT he occurrence of a ventricular septal defect (VSD) after a myocardial infarction (MI) is an infrequent but serious sequela, which usually occurs within the first week.1 In the years before reperfusion became available, the incidence of VSD after an MI was between 1% and 2%, with an in-hospital mortality rate of 45% with surgery, and 90% with medical managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Therapeutically, studies on mice have revealed successful inhibition of CR by anti-in ammatory therapies 41 , or use of some currently routine medications like anti-platelet drugs, ARB or ACEI 36 . Collectively, our ndings on patients with CR are supported in part by studies in the mouse model of CR regarding signi cance of infarct size, age 42 , in ammation 39,41 and histopathology of type-III CR 9,23 . Further research is required to illustrate the mechanism of early CR and test therapeutic interventions.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Therapeutically, studies on mice have revealed successful inhibition of CR by anti-in ammatory therapies 41 , or use of some currently routine medications like anti-platelet drugs, ARB or ACEI 36 . Collectively, our ndings on patients with CR are supported in part by studies in the mouse model of CR regarding signi cance of infarct size, age 42 , in ammation 39,41 and histopathology of type-III CR 9,23 . Further research is required to illustrate the mechanism of early CR and test therapeutic interventions.…”
Section: Discussionsupporting
confidence: 59%
“…A signi cant body of knowledge has been generated by preclinical studies on the mechanism and therapeutic intervention of CR. These studies were entirely conducted in the mouse as the only laboratory species that develop CR post transmural MI like human patients 9,23,36 . Mechanistically, CR occurred in mice within a single onset peak timing (days 3-5) together with wall thinning and ventricular dilatation 23 , simulating the human type-III rupture but without CR event within the rst 24 hours, which differs from our clinical nding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of CR patients is complex and might require a variety of therapeutic approaches, including pharmacologic (include ACEI, β-blocker, intravenous nitrates, and hydralazine) and device-based therapies to achieve afterload reduction and hemodynamic stabilization. Whilst medical therapy and non-pharmacologic methods may only stabilize CR patients, the treatment of choice is closure of rupture site by surgical and catheter-based means [ 25 , 26 ]. The outcome of operated CR patients is closely related to their hemodynamic state prior to the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…7 VA ECMO has been reported as a bridge to percutaneous closure and surgical repair. 8,9 Percutaneous VSD closure may be optimal in smaller VSDs (#15 mm), though larger defects, such as the one in this case, have been successfully repaired. 10 Some operators prefer to advance the occluder from the venous side via the internal jugular vein, as there may be less tension on the friable VSD borders through this method.…”
Section: Video Highlightsmentioning
confidence: 95%